2019
DOI: 10.3390/polym11121971
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PLLA/C3S Composite Membrane for the Prevention of Bone Cement Leakage

Abstract: Kyphoplasty is an important treatment for stabilizing spine fractures due to osteoporosis. However, leakage of polymethyl-methacrylate (PMMA) bone cement during this procedure into the spinal canal has been reported to cause many adverse effects. In this study, we prepared an implantable membrane to serve as a barrier that avoids PMMA cement leakage during kyphoplasty procedures through a hybrid composite made of poly-l-lactic acid (PLLA) and tricalcium silicate (C 3 S), with the addition of C 3 S into PLLA ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The implantable membrane was utilized as a barrier to provide a conducive microenvironment for promoting high osteogenic activity and encouraging recruitment of osteoprogenitors within the defect, 37 as well as for enhancing mechanical and anti-degradation properties. 38,39 In this study, the observed positive alveolar ridge preservation effects of the polarized versus PTFE group might be attributed to the membrane surface charge restoring the electrical microenvironment in the dental alveolar socket, thereby enhancing osteoblast activity and bone regeneration, as demonstrated in our previous studies. 14,15 Our results are also consistent with other studies which reported that polarized BTO/P(VDF-TrFE) membrane enhanced osteoblast differentiation and promoted bone defect healing in animals with osteoporosis-like symptoms.…”
Section: Discussionsupporting
confidence: 67%
“…The implantable membrane was utilized as a barrier to provide a conducive microenvironment for promoting high osteogenic activity and encouraging recruitment of osteoprogenitors within the defect, 37 as well as for enhancing mechanical and anti-degradation properties. 38,39 In this study, the observed positive alveolar ridge preservation effects of the polarized versus PTFE group might be attributed to the membrane surface charge restoring the electrical microenvironment in the dental alveolar socket, thereby enhancing osteoblast activity and bone regeneration, as demonstrated in our previous studies. 14,15 Our results are also consistent with other studies which reported that polarized BTO/P(VDF-TrFE) membrane enhanced osteoblast differentiation and promoted bone defect healing in animals with osteoporosis-like symptoms.…”
Section: Discussionsupporting
confidence: 67%
“…Tricalcium silicate is the main component of Portland cement. This material can provide sufficient mechanical strength after hydrolyzation [11] and excellent biocompatibility for bone cement application [12][13][14][15]. Furthermore, it Senthilkumar Thirumurugan and Yu-Chien Lin contributed equally to this paper.…”
Section: Introductionmentioning
confidence: 99%
“…154,155 Some novel biomaterials exhibited appreciable effects in preventing the leakage of PMMA, such as high-viscosity cement, [156][157][158] and composite membranes. 159,160 Comprehending probable complications can optimize treatment options, innovate techniques, guide perioperative management, and provide a credible reference for researchers in the future.…”
mentioning
confidence: 99%